2005
DOI: 10.1093/ndt/gfi012
|View full text |Cite
|
Sign up to set email alerts
|

Withholding or withdrawing dialysis in the elderly: the perspective of a western region of France

Abstract: This study has shown that refusing or discontinuing dialysis are practices accepted by the vast majority of nephrologists in one region of France. Patient refusal is not a basis for denial or discontinuation of dialysis in elderly patients. Our investigation has demonstrated a consensus regarding decisions to refuse or discontinue dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…However, it is not clear that CM is adequately discussed as a viable treatment option in the United States (12,13). Reasons for this may include providers' uncertainty about patient prognosis, a relative lack of evidence of its efficacy compared with dialysis, and providers' personal values, which may prioritize survival over quality of life (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear that CM is adequately discussed as a viable treatment option in the United States (12,13). Reasons for this may include providers' uncertainty about patient prognosis, a relative lack of evidence of its efficacy compared with dialysis, and providers' personal values, which may prioritize survival over quality of life (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The thought of making the ‘wrong decision’ haunts every clinician and studies of physicians’ attitudes show that individual physician comfort with recommending against dialysis varies both with age and experience [21]. Interestingly, a substantial number of physicians surveyed expressed regret over one or more previous decisions to offer or withhold dialysis.…”
Section: Patient Selectionmentioning
confidence: 99%
“…[17][18][19] Patient variables including age, functional status, socioeconomic status, and preferences have been shown to be associated with physician decisions. 22,26 In several of these studies, patient age is a factor in decisions to withhold dialysis (i.e., increasing age associated with greater likelihood to withhold dialysis). [18][19][20][21][22][23][24][25][26][27] Retrospective studies of dialysis patients have also found patient variables to be important.…”
Section: Referral Decisions For Dialysis Initiationmentioning
confidence: 99%